Investigation on the stable and stick-slip crack propagation behaviors in double cantilever beam test. Issue 13 (2nd October 2020) - Guo, Sai; Xia, Yong; Wei, Xinqi; Zhou, Qing
ABSTRACT: The stable and stick-slip crack propagation behaviors with pure cohesive fracture are observed in the adhesively bonded AA7075-T6 double cantilever beam tests using Henkel Terokal 5089 and Darbond EP-1506 structural adhesives. The ratio of the fracture toughness between the fast crack propagation stage and initiation stage is found to be a key factor that governs the fracture behavior. A theoretical model based on the energy conservation is established to quantitatively predict the crack length in the fast propagation stage using the pre-described ratio. A new parameter is proposed to characterize the fracture toughness of adhesive that exhibits stick-slip fracture behavior. The finite element simulation with cohesive zone model and an innovative technique is performed to successfully mimic the stick-slip fracture behavior, as the simulated load versus opening displacement curve agrees well with the test result. The mechanism of the stick-slip fracture behavior is justified from mechanical and material science aspects. Given that the fracture toughness in crack initiation stage is greater than that in propagation stage, methods to arrest the crack in propagation stage and get it back to initiation stage deserve further investigations, which could be an effective way to enhance the fracture resistance of the adhesively bonded joints.